A structured methodology for the direction and planningphase of the cyber threat intelligence cycle : reducinginformational noise and aligning with the regulatoryframework of the brazilian national financial system - Gontijo, Pedro Henrique Silva (2026)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, Programa de Pós-Graduação Profissional em Engenharia Elétrica, 2026.